Cathodic protection construction method of concrete structure
By removing the water-repellent ventilation layer and applying a pretreatment liquid with an electrolyte and wetting agent, followed by direct anode installation, the method achieves efficient corrosion protection in concrete structures with high chloride ion concentration, overcoming the inefficiencies of existing methods.
Patent Information
- Application Number
- JP2023112406
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-20
AI Technical Summary
The surface impregnation method in concrete structures with high chloride ion concentration fails to provide effective corrosion protection due to high electrical resistance of the water-repellent ventilation layer, making it difficult for corrosion prevention current to flow, and the additional application of cathodic protection methods is inefficient without removing the existing layer.
A method involving the removal of the water-repellent ventilation layer and application of a pretreatment liquid containing an electrolyte and wetting agent, followed by direct installation of an anode unit, ensuring a lower electrical resistance and effective corrosion protection without forming a new ventilation layer.
This approach provides high corrosion protection with simpler steps and lower costs by ensuring sufficient corrosion prevention current flow without the need for extensive repair work or forming a new ventilation layer.
Smart Images

Figure 2025009411000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a cathodic protection method for a concrete structure, and more particularly to a technique for additionally applying a cathodic protection method to a concrete structure to which a surface impregnation method has already been applied. [Background technology]
[0002] In concrete structures containing steel materials such as reinforcing bars, PC steel wires, and steel frames, chloride ions, water, oxygen, and the like may penetrate and permeate the interior of the structure, causing corrosion of the steel materials, which may then cause the deterioration of the structure to progress, eventually resulting in a significant decrease in various performance properties such as the strength of the structure. Therefore, various means have been developed to prevent corrosion of steel materials in concrete structures, and one of these means is a method that combines cathodic protection and surface impregnation methods (hereinafter also referred to as the "combined cathodic protection and surface impregnation method"). Cathodic protection is a method of protecting against corrosion by changing the potential of the steel (cathode) to a more base potential by using the steel in a concrete structure as the cathode and passing a protective current between the cathode and an anode installed on the surface of the concrete structure or in a groove cut into the surface. There are two types of cathodic protection: the galvanic anode method and the external power supply method. The galvanic anode method is a method in which a battery is created using a base metal that has a higher ionization tendency than the steel, which serves as the cathode, as the anode, and a protective current is passed due to the potential difference between the two electrodes. On the other hand, the external power supply method is a method in which a DC power supply is used to pass a protective current from the anode to the cathode (steel). The surface impregnation method is a method of applying a surface impregnation material to the surface of a concrete structure to form a water-repellent, breathable layer on the surface layer of the concrete, thereby suppressing the penetration of chloride ions, water, etc. from the outside. Known surface impregnation materials include silane-based (water-repellent type) and silicate-based (densified type) materials, as well as combinations of these.
[0003] Patent Documents 1 and 2 describe a method for applying a surface impregnation material to the surface of a concrete structure that has been subjected to cathodic protection using an external power source method or a galvanic anode method, as a combined cathodic protection and surface impregnation method. The concrete structure is constructed by installing an anode material covered with a coating material such as cement mortar on a concrete body in which steel materials are embedded, and the surface impregnation material is applied to the surface of the coating material and the surface of the concrete body around it. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2011-236485 A [Patent Document 2] JP 2012-144771 A Summary of the Invention [Problem to be solved by the invention]
[0005] The surface impregnation method has a problem that when it is applied in a state where the chloride ion concentration in the concrete structure is high, it is difficult to obtain a corrosion inhibition effect, and the steel material in the concrete structure corrodes after the application. As a countermeasure to this problem, it is possible to additionally apply cathodic protection to a concrete structure to which only the surface impregnation method has been applied as a corrosion prevention means, that is, a concrete structure in which a water-repellent air-permeable layer made of a surface impregnation material has been formed on the surface. In other words, it is a change from the surface impregnation method to a combined cathodic protection and surface impregnation method as described in Patent Documents 1 and 2. As a specific method, a method of installing an anode on the surface of an existing water-repellent air-permeable layer in a concrete structure can be mentioned. However, since the water-repellent air-permeable layer has a large electric resistance value, simply installing an anode on the surface of the existing water-repellent air-permeable layer does not allow a sufficient anticorrosive current to flow between the anode and the steel material to be protected from corrosion, which may result in little meaning in additionally applying cathodic protection. Therefore, it is possible to install an anode after removing the existing water-repellent air-permeable layer. Specifically, a method is exemplified in which the surface layer of a concrete structure, including a water-repellent and air-permeable layer, is removed from the concrete structure to secure an installation space, a concrete repair material such as non-shrink mortar is applied to the installation space to compensate for the thickness of the removed surface layer, an anode is installed in the installation space, and a surface impregnation material is applied to the outer surface of the anode to form a water-repellent and air-permeable layer, thereby compensating for the removal of the existing surface impregnation material. However, such work includes a relatively large number of steps, since it includes not only the work of securing the installation space and the work of installing the anode, but also the work of repairing the installation space and the work of applying the surface impregnation material to the installed anode, and further, these repair and application works can be large-scale depending on the scale of the cathodic protection method, and therefore there is a problem that it is complicated and the construction cost is high.
[0006] Therefore, an object of the present invention is to provide an electric corrosion protection method for a concrete structure which can obtain a high corrosion protection effect with a relatively simple process. [Means for solving the problem]
[0007] The present invention provides a method for cathodic protection of a concrete structure, comprising: a concrete body in which a steel material is embedded; and a water-repellent, breathable layer provided on the surface of the concrete body, the water-repellent, breathable layer including a silane-based or silane-siloxane-based surface impregnation material, a pretreatment step of removing a surface layer including the water-repellent and air-permeable layer from the concrete structure, or applying a pretreatment liquid including an electrolyte and a wetting agent that modifies the surface wettability of the water-repellent and air-permeable layer to the surface of the concrete structure; an anode installation step of directly installing an anode unit including an anode material on the portion of the concrete structure that has been subjected to the pretreatment step, and electrically connecting the anode material and the steel material; This is an electric corrosion protection method for a concrete structure, in which the water-repellent air-permeable layer is not formed in an area of the concrete structure that overlaps in plan view with the anode unit installed in the anode installation step.
[0008] The present invention also provides an electric corrosion protection structure for a concrete structure manufactured by the electric corrosion protection method of the present invention, This is an electrochemical protection structure for a concrete structure, in which the contact portion between the anode unit and the surface of the concrete structure is ground off, or the contact portion has a higher content of the wetting agent than the surrounding area of the contact portion on the surface. Effect of the Invention
[0009] According to the present invention, there is provided a cathodic protection method for concrete structures which can obtain a high corrosion protection effect through a relatively simple process. [Brief description of the drawings]
[0010] [Figure 1]FIG. 1 is an explanatory diagram of one embodiment of the cathodic protection method for concrete structures of the present invention, in which FIG. 1(a) is a cross-sectional view that shows a schematic cross-section along the thickness direction of a concrete structure to which the cathodic protection method is applied, FIG. 1(b) is a cross-sectional view that shows a schematic cross-sectional view of the concrete structure shown in FIG. 1(a) undergoing a pretreatment process and removing its surface layer, and FIG. 1(c) is a cross-sectional view that shows a schematic cross-sectional view of the cathodic protection structure obtained by performing an anode installation process on the concrete structure shown in FIG. 1(b). [Diagram 2] FIG. 2 is a schematic perspective view of the installation side of the anode unit in the cathodic protection structure shown in FIG. [Diagram 3] FIG. 3 is a cross-sectional view that typically shows a cross section along the thickness direction of another embodiment of the cathodic protection structure for a concrete structure of the present invention. [Figure 4] FIG. 4 is a schematic perspective view of a mortar specimen used in investigating the relationship between the impregnation depth of the surface impregnating material and the electrical resistance value. [Diagram 5] FIG. 5 is a graph substituting a drawing showing a grinding depth-electrical resistance curve for Sample A (without application of a surface impregnation material) using the mortar test piece shown in FIG. [Figure 6] FIG. 6 is a graph substituting a drawing showing a grinding depth-electrical resistance curve for sample B (with surface impregnation material applied) using the mortar test piece shown in FIG. [Figure 7] FIG. 7 is a graph substituting a drawing showing a grinding depth-electrical resistance curve for sample C (with surface impregnation material applied) using the mortar test piece shown in FIG. [Figure 8] FIG. 8 is a graph showing the results of a measurement test of current density for the cathodic protection structure of the example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] 1(a) shows a concrete structure 1 to which one embodiment of the cathodic protection method for concrete structures of the present invention (hereinafter, simply referred to as "cathodic protection method") is applied. The concrete structure 1 has a concrete body 3 in which a steel material 2 is embedded, and a water-repellent, breathable layer 4 provided on the surface of the concrete body 3.
[0012] The steel material 2 may be, for example, reinforcing bars or steel frames. The concrete body 3 is a structure constructed using concrete, and examples thereof include river structures such as roads, bridges, tunnels, ports, airports, dams, and embankments; various buildings such as houses, buildings, and commercial facilities; and the like.
[0013] The water-repellent and breathable layer 4 contains at least a silane-based or silane-siloxane-based surface impregnation material. The water-repellent and breathable layer 4 is typically formed by applying a solvent-based, water-based or solventless paint containing the surface impregnation material to the surface of the concrete body 3. The silane-based surface impregnation material contains a silane monomer represented by the following general formula (1) but does not contain a silane oligomer represented by the following general formula (2). The silane-siloxane-based surface impregnation material contains a silane oligomer represented by the following general formula (2). Any known surface impregnation material can be used without any particular restrictions.
[0014] [ka] In the formulas (1) and (2), R1 represents an alkyl group, and R2 represents an alkoxy group. In the formula (2), n represents a natural number of 1 to 10.
[0015] The surface impregnating material is fixed to the concrete body 3 by chemically bonding with the hydroxyl groups on the surface of the concrete body 3, thereby forming the water-repellent and air-permeable layer 4. In the water-repellent and air-permeable layer 4, the alkyl groups, which are hydrophobic groups, are oriented opposite the concrete body 3, so the water-repellent and air-permeable layer 4 has water repellency. In addition, the water-repellent and air-permeable layer 4 has air permeability and does not block the pores that the concrete body 3 originally has, so the concrete structure 1 can release water vapor generated inside the concrete body 3 to the outside through the water-repellent and air-permeable layer 4.
[0016] The thickness of the water-repellent, breathable layer 4 (the thickness of the water-repellent, breathable layer 4 before the present invention is applied) is not particularly limited, but is typically preferably 1 to 8 mm, more preferably 2 to 7 mm.
[0017] The thickness of the water-repellent and breathable layer 4 can be measured by a method conforming to JSCE-K571-2013 (Testing method for surface impregnating materials). Specifically, after immersing the concrete structure 1 in water, the concrete structure 1 is taken out of the water and the cross section along the thickness direction is visually observed, and the part that has not changed color compared to before immersion is regarded as the water-repellent and breathable layer 4, and the thickness of this part is measured using a measuring instrument such as a vernier caliper.
[0018] The cathodic protection method of this embodiment includes a pretreatment step (see FIG. 1(b)) of subjecting concrete structure 1 to pretreatment, and an anode installation step (see FIG. 1(c)) of directly installing an anode unit 6 including an anode material 61 on a pretreated area 5, which is the part of concrete structure 1 that has been subjected to the pretreatment step, and electrically connecting the anode material 61 to steel material 2. FIG. 2 shows the installation side of the anode unit 6 in a cathodic protection structure 10 obtained through these steps.
[0019] The pretreatment step is a step for securing an installation space for the anode unit 6 on the concrete structure 1, and the pretreatment area 5 is the installation space. The area to which the pretreatment step is applied is typically equal to or greater than the area of the contact surface (lower surface) of one anode unit 6 with the concrete structure 1. When a plurality of anode units 6 are installed on the surface of the concrete structure 1 as shown in FIG. 2, the area is equal to or greater than the area of the contact surface multiplied by the number of anode units 6 installed. The anode unit 6 of this embodiment has a rectangular parallelepiped shape as shown in FIG. 2. For example, when the contact surface of the anode unit 6 with the concrete structure 1 is a rectangle in plan view with a longitudinal length of 1000 mm and a lateral length of 10 to 150 mm, the area to which the pretreatment step is applied is 10,000 to 150,000 mm per one anode unit 6. 2 That's all.
[0020] If the pre-treated part 5 is exposed to the external environment, there is a risk that moisture, chlorine components, etc. will penetrate into the interior of the concrete structure 1 (electrical corrosion protection structure 10) through the pre-treated part 5, resulting in an adverse effect on the corrosion protection effect. Therefore, in order to prevent this, it is preferable that the entire surface of the pre-treated part 5 is covered by the anode unit 6.
[0021] The pretreatment step is a step of removing the surface layer including the water-repellent and air-permeable layer 4 from the concrete structure 1, i.e., an area separated by a predetermined distance in the thickness direction from the surface of the water-repellent and air-permeable layer 4 that forms the surface of the concrete structure 1 (hereinafter also referred to as the "surface layer removing step"), or applying a pretreatment liquid to the surface of the concrete structure 1 (hereinafter also referred to as the "pretreatment liquid applying step"). In the present invention, in the pretreatment step, 1) only the surface layer removing step may be performed, 2) only the pretreatment liquid applying step may be performed, or 3) both the surface layer removing step and the pretreatment liquid applying step may be performed. In the case of 3), in the pretreatment step, it is preferable to remove the surface layer from the concrete structure 1 and then apply a pretreatment liquid to the portion from which the surface layer has been removed.
[0022] In the surface layer removing step, at least the water-repellent and air-permeable layer 4 forming the surface of the concrete structure 1 is removed, and further, the surface layer of the concrete body 3 adjacent to the water-repellent and air-permeable layer 4 in the thickness direction may be removed. In a preferred embodiment of the cathodic protection method of the present invention, the amount of the surface layer of the concrete structure 1 to be removed in the surface layer removing step is at least 1.0 mm in thickness, as described below, and further, 0.05 mm is sufficient when the pretreatment liquid application step is performed. On the other hand, since the thickness of the existing water-repellent and air-permeable layer 4 usually exceeds 1.0 mm, typically, only the water-repellent and air-permeable layer 4 is removed in the surface layer removing step. Thus, since the amount of the surface layer to be removed in the surface layer removing step is relatively small, cutting means such as a blade or drill, which are used when the portion to be removed is relatively large, are basically unnecessary as the surface layer removing means used in the surface layer removing step, and grinding means are appropriate. Examples of the grinding means include blasting processes such as sandblasting and steel shot blasting; water jet, disc sander, abrasive paper, and wire brush. In this embodiment, as shown in FIG. 1(b), a blasting process is performed in which granular abrasive P is projected from a blasting device BM onto the water-repellent and breathable layer 4 of the concrete structure 1, colliding the layer with the layer, thereby removing the water-repellent and breathable layer 4 from the concrete structure 1 and forming a pre-treated area 5.
[0023] The pretreatment liquid used in the pretreatment liquid application step contains an electrolyte and a wetting agent that modifies the surface wettability of the water-repellent, breathable layer 4 . Examples of the electrolyte include magnesium chloride, calcium chloride, and lithium chloride. In the present invention, one type of electrolyte can be used alone or two or more types of electrolytes can be used in combination. In particular, magnesium chloride is preferably used as the electrolyte in the present invention because it has deliquescent properties. The wetting agent is preferably a silicone surfactant. Examples of the silicone surfactant include organopolysiloxanes modified with hydrophilic groups, such as polyoxyethylene (POE)-modified organopolysiloxane, polyoxyethylene-polyoxypropylene (POE-POP)-modified organopolysiloxane, POE sorbitan-modified organopolysiloxane, and POE glyceryl-modified organopolysiloxane, and the like. These may be used alone or in combination of two or more.
[0024] The content of the electrolyte in the pretreatment liquid is preferably 5 to 30% by mass, and more preferably 10 to 20% by mass, based on the total mass of the pretreatment liquid. The content of the wetting agent in the pretreatment liquid is preferably 0.02 to 2.0% by mass, and more preferably 0.5 to 1.0% by mass, based on the total mass of the pretreatment liquid.
[0025] The pretreatment liquid typically contains a solvent in addition to the electrolyte and wetting agent. The solvent may be any solvent that has fluidity at room temperature and normal pressure and in which the electrolyte and wetting agent can be dissolved or dispersed, and is typically water. The pretreatment liquid may contain other components in addition to the above components (electrolyte, wetting agent, and solvent). Examples of the other components include a carboxyl group-containing polymer modified product as a dispersant. By including the dispersant in the pretreatment liquid, the dispersibility of the electrolyte or wetting agent in the pretreatment liquid can be improved.
[0026] The target to which the pretreatment liquid is applied in the pretreatment liquid application step is the existing water-repellent, breathable layer 4 that forms the surface of the concrete structure 1 if the pretreatment step does not include the surface layer removal step, and, if the pretreatment step includes the surface layer removal step, the pretreatment step is preferably carried out after the surface layer removal step, so the target to which the pretreatment liquid is applied is the portion of the concrete structure 1 from which the surface layer has been removed by the surface layer removal step.
[0027] In the pretreatment liquid application step, the method for applying the pretreatment liquid is not particularly limited, and examples thereof include a method of applying the pretreatment liquid using a known liquid applicator such as a brush or a roller, and a method of spraying the pretreatment liquid using a sprayer.
[0028] The electrical resistance value (surface resistivity) of the pre-treated portion 5, which is the portion of the concrete structure 1 that has been subjected to the pre-treatment process, is preferably 1 to 100 kΩ·cm, and more preferably 1 to 50 kΩ·cm. When the electrical resistance value of the pre-treated portion 5 is within the above range, the flow of anticorrosive current between the anode material 61 of the anode unit 6 installed in the pre-treated portion 5 and the steel material 2 becomes good, and a sufficient anticorrosive effect can be obtained. The electrical resistance value (surface resistivity) of the pre-treated portion 5 can be measured by a method in accordance with JSCE-G581-2018 (Draft method for testing electrical resistivity of concrete by four-electrode method). As described above, the pretreatment step includes the surface layer removal step and / or the pretreatment liquid application step, and these steps are preferably performed so that the electrical resistance of the pre-treated area 5 after the pretreatment step is 1 to 100 kΩ cm.
[0029] According to the findings of the present inventors, when the surface layer removing step is carried out in the pretreatment step to remove the surface layer including the water-repellent and breathable layer 4 from the concrete structure 1 (including the case where the pretreatment liquid application step is further carried out), in order to set the electrical resistance value of the pretreated portion 5 to 1 to 100 kΩ·cm, the amount of the surface layer to be removed from the concrete structure 1 is preferably 1.0 mm or more, more preferably 1.5 mm or more, in terms of the thickness of the surface layer. On the other hand, the upper limit of the amount of the surface layer to be removed from the concrete structure 1 is preferably 8.0 mm or less, more preferably 7.3 mm or less, in terms of the thickness of the surface layer. The findings will be described in detail later.
[0030] When the pretreatment liquid application step is carried out in the pretreatment step, and the pretreatment liquid is applied to the surface of the concrete structure 1, the electrolyte is preferably applied to the pretreatment area 5 at a concentration of 5 g / m from the viewpoint of making the electrical resistance value of the pretreatment area 5 1 to 100 kΩ·cm. 2More preferably, 10 g / m 2 or more, and the wetting agent is preferably applied in an amount of 0.02 g / m 2 More preferably, 0.05 g / m 2 On the other hand, the upper limit of the amount of the electrolyte to be applied is preferably 30 g / m 2 Less than 20 g / m 2 The upper limit of the amount of the wetting agent applied is preferably 2.0 g / m 2 Less than 1.0 g / m, more preferably 1.0 g / m 2 The preferred amounts of the electrolyte and wetting agent to be applied can be adjusted by adjusting the composition of the pretreatment liquid, the amount to be applied to the concrete structure 1, and the like.
[0031] In the case where both the surface layer removing step and the pretreatment liquid applying step are carried out in the pretreatment step, that is, in the case where the surface layer is removed from the concrete structure 1 and then the pretreatment liquid is applied to the part from which the surface layer has been removed, the amount of the surface layer removed in the surface layer removing step is preferably 0.05 mm or more, more preferably 0.05 to 2.0 mm, in terms of the thickness of the surface layer, and in the pretreatment liquid applying step, the electrolyte is preferably applied to the part from which the surface layer has been removed in an amount of 5 to 30 g / m 2 , more preferably 10 to 20 g / m 2 The wetting agent is preferably used in an amount of 0.02 to 2.0 g / m 2 , more preferably 0.5 to 1.0 g / m 2 It is preferable to give
[0032] In the cathodic protection method of the present invention, in the anode installation step, an anode unit 6 is installed directly on the pretreated area 5, which is the part of the concrete structure 1 that has been subjected to the pretreatment step. This results in a cathodic protection structure 10, which is one embodiment of the cathodic protection structure of the present invention. As shown in FIG. 2, the cathodic protection structure 10 has a plurality of anode units 6 arranged intermittently on the surface of the concrete structure 1, and each of the plurality of anode units 6 is installed on the surface of the concrete structure 1 by the cathodic protection method of the present invention described above. In other words, the cathodic protection structure 10 is manufactured by carrying out a series of installation steps (the pretreatment step and the anode installation step) in the same number as the number of anode units 6 installed.
[0033] The term "direct installation" means that no other member is interposed between the pretreated portion 5 and the anode unit 6. In other words, in the present invention, even if the pretreatment step is performed on the concrete structure 1 and then the surface layer removal step is performed on the pretreated portion 5 in the pretreatment step to remove the surface layer of the concrete structure 1, no repair work is performed to make up for the thickness of the removed surface layer using a repair material for the concrete part of the concrete body 3 such as non-shrink mortar or a surface impregnation material which is the material of the water-repellent and breathable layer 4.
[0034] In addition, in the cathodic protection method of the present invention, the water-repellent and air-permeable layer 4 is not formed in the area of the concrete structure 1 that overlaps with the anode unit 6 installed in the anode installation step in a plan view, in other words, in the area that overlaps with the projected image of the anode unit 6 when projected in the thickness direction of the concrete structure 1. That is, in the present invention, the water-repellent and air-permeable layer 4 is not formed by directly applying a surface impregnation material to the outer surface of the anode unit 6 installed in the concrete structure 1 (cathodic protection structure 10), and the coating material such as cement mortar and a surface impregnation material are not applied in this order to the outer surface of the anode unit 6, and the coating material and the water-repellent and air-permeable layer 4 are not laminated on the outer surface of the anode unit 6. Such a configuration of the cathodic protection method of the present invention is in contrast to the techniques described in Patent Documents 1 and 2, in which a water-repellent and air-permeable layer is formed by applying a surface impregnation material to a coating material that covers an anode installed in a concrete structure.
[0035] In the cathodic protection method of the present invention, once the pre-treated area 5, which is the installation space for the anode unit 6, is formed in the concrete structure 1 by carrying out the pretreatment step, the anode unit 6 is directly installed in the pre-treated area 5, and the water-repellent and breathable layer 4 that directly or indirectly covers the installed anode unit 6 is not newly formed. It is natural for a person skilled in the art to think that the existing configuration of the concrete structure, such as the water-repellent and breathable layer, should be repaired after the installation of the anode unit. In particular, when the surface layer of the concrete structure is removed by carrying out the surface layer removal step in the pretreatment step, it is likely to be considered important to obtain an anticorrosive effect by repairing the removed portion by applying a surface impregnating material to the entire installation location of the anode unit to form a water-repellent and breathable layer, etc. However, the cathodic protection method of the present invention is characterized in that it does not carry out repair work on the concrete structure even when the surface layer removal step is carried out in the pretreatment step. As a result, the cathodic protection method of the present invention has the characteristic that a high anticorrosive effect can be obtained by a relatively simple process. An electrochemical protection structure manufactured by the electrochemical protection method of the present invention, represented by electrochemical protection structure 10, typically has the entire surface of the pre-treated area 5 formed by carrying out the pretreatment process covered by the anode unit 6, and the anode unit 6 isolates the pre-treated area 5 from the external environment, so that it can exhibit a sufficient anti-corrosion effect without forming a new water-repellent and breathable layer 4 that directly or indirectly covers the anode unit 6.
[0036] The anode unit 6 includes at least an anode material 61. As the anode material 61, any anode material commonly used in cathodic protection methods can be used without any particular restrictions. Examples of anode materials for cathodic protection using a galvanic anode system include aluminum, zinc, magnesium, and alloys thereof. Examples of anode materials for cathodic protection using an external power source system include a titanium substrate coated with an oxide, or a carbon fiber coated with nickel. Examples of the oxide include one or more metals selected from the platinum group metals such as platinum, palladium, rhodium, iridium, and ruthenium.
[0037] The shape of the anode unit 6 is typically determined by the shape of the anode material 61 disposed therein. In this embodiment, the anode material 61 has a shape that is long in one direction (specifically, a strip shape), and the anode unit 6 including the anode material 61 also has a shape that is long in one direction, similar to the anode material 61, as shown in Fig. 2. In addition, for example, when the anode material 61 is a flat panel type that is commonly used in cathodic protection using a galvanic anode method, the shape of the anode unit 6 including the anode material 61 is typically flat, similar to the anode material 61.
[0038] As shown in FIG. 1(c), the anode unit 6 of this embodiment includes an anode material 61, a core metal 62 that penetrates the inside of the anode material 61 and extends over the entire length of the anode material 61 in the longitudinal direction, a backfill 63 that surrounds the anode material 61 and is in electrical contact with it, and a container 64 that contains and protects the anode material 61 and the backfill 63. The container 64 is a trough-shaped container that contains the anode material 61 and the backfill 63, has a container part 64a with an opening, and a pair of flange parts 64b, 64b that extend outward from the edge of the opening, and is fixed to the surface of the concrete structure 1 by a fixing device 65 such as a pin or an anchor bolt via the flange part 64b with the opening arranged to face the pre-treated part 5. When the anode unit 6 is fixed to the surface of the concrete structure 1 in this manner, the backfill 63 comes into contact with the pre-treated part 5 through the opening of the container part 64a. The portion of the fixture 65 that is embedded in the concrete structure 1 is inserted into the hollow portion of a hollow resin plug 66 , and is insulated from the concrete structure 1 .
[0039] The backfill 63 is employed in the anode unit 6 for the purpose of lowering the ground resistance of the anode material 61, improving the electrochemical properties of the anode material 61, etc. As the backfill 63, any material used for the above-mentioned purpose in this type of cathodic protection structure can be used without any particular limitation, and examples thereof include a water-retentive material obtained by impregnating a cellulosic fiber aggregate (water-absorbing material) with an aqueous magnesium chloride solution; a paste containing bentonite and magnesium chloride; a mixture of magnesium chloride, cement, and water; an absorbent polymer that has absorbed an aqueous strong alkaline solution; and one or more carbonaceous materials selected from coke, carbon black, graphite, and carbon fiber.
[0040] The material of the container 64 can be any material that has been used as a container for backfill in the past, without any particular restrictions, and examples of such materials include weather-resistant polyvinyl chloride, polyester, epoxy, polystyrene, polyethylene, polypropylene, acrylic, polycarbonate, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyether ether ketone (PEEK), and other resins; metals such as titanium and stainless steel; fiberglass reinforced plastic (FRP), glass, and ceramics.
[0041] In the anode installation step, an anode unit 6 is directly installed in the pretreated portion 5 of the concrete structure 1, and then an anode material 61 of the anode unit 6 and the steel material 2 are electrically connected to each other. In this embodiment, a galvanic anode method is adopted as the cathodic protection method, and accordingly, as shown in FIG. 2, the steel material 2 and the anode material 61 are connected by a conductor 7. In the present invention, it is also possible to adopt an external power supply method as the cathodic protection method. In that case, a direct current power supply device (not shown) is connected to the steel material 2 and the anode material 61 by a conductor 7. By electrically connecting the anode material 61 and the steel material 2 in this manner, it becomes possible to pass an anticorrosive current from the anode material 61 to the steel material 2, and it becomes possible to prevent corrosion of the steel material 2.
[0042] 3 shows a cathodic protection structure 10A which is another embodiment of the cathodic protection structure for a concrete structure of the present invention. Regarding the cathodic protection structure 10A, the configurations different from the above-mentioned embodiment (cathodic protection structure 10) will be mainly described, and the same configurations will be given the same reference numerals and will not be described. For the configurations of the cathodic protection structure 10A that are not specifically described, the description of the above-mentioned embodiment (cathodic protection structure 10) will be applied as appropriate.
[0043] The cathodic protection structure 10A differs from the cathodic protection structure 10 in the configuration of the anode unit 6. That is, the anode unit 6 of the cathodic protection structure 10A does not have a container for the anode material 61, such as a container 64 (see FIG. 1(c)), and the anode material 61 is exposed, with a flat backfill 63 interposed between the exposed anode material 61 and the pre-treated portion 5. The dimensions of the anode material 61 in a plan view are larger than those of the backfill 63, and the entire surface (upper surface) of the backfill 63 opposite the concrete body 3 is covered with the anode material 61. The anode unit 6 of the cathodic protection structure 10A is also disposed between the anode material 61 and the pre-treated portion 5, and has an outflow prevention material 69 surrounding the backfill 63. The outflow prevention material 69 is for preventing the backfill 63 from flowing out of the pretreatment area 5, and is made of a polyurethane or polyethylene foam or a rubber material from the viewpoints of flexibility, water stoppage, and durability. In the cathodic protection structure 10A, similarly to the cathodic protection structure 10, a plurality of anode units 6 are installed on the surface of the concrete structure 1, and a fixing base material 67 is fixed to the surface of the concrete structure 1 between two adjacent anode units 6, 6 by a fixing device 65, and the anode material 61 of each of the two anode units 6, 6 is fixed to the fixing base material 67 by a fixing device 68 such as a screw. The fixing base material 67 is in contact with the outflow prevention material 69 of each of the two anode units 6, 6. Although the anode unit 6 of the electrical corrosion protection structure 10A does not have a container for the anode material 61, similarly to the electrical corrosion protection structure 10, the anode unit 6 isolates the pre-treated area 5 from the external environment, and therefore a sufficient corrosion protection effect can be achieved without forming a new water-repellent and breathable layer 4 that directly or indirectly covers the anode unit 6.
[0044] The present invention includes an electrochemical protection structure for a concrete structure (hereinafter, also simply referred to as "electrochemical protection structure") manufactured by the electrochemical protection method of the present invention. Unless otherwise specified, the explanation of the electrochemical protection method of the present invention described above is appropriately applied to the electrochemical protection structure of the present invention.
[0045] The above-mentioned cathodic protection structure 10 (see FIG. 1(c)) and cathodic protection structure 10A (see FIG. 3) are both embodiments of the cathodic protection structure of the present invention. The cathodic protection structures 10, 10A are characterized in that the contact portion (pre-treated portion 5) with the anode unit 6 on the surface of the concrete structure 1 is a) in a ground state, or b) the contact portion (pre-treated portion 5) has a higher wetting agent content than the surrounding area of the contact portion on the surface of the concrete structure 1. The wetting agent of b) is one of the essential components of the pretreatment liquid.
[0046] Regarding a), it is possible to determine whether the contact portion (pre-treated portion 5) is in a ground state by comparing the surface smoothness of the contact portion and the periphery of the contact portion on the surface of the concrete structure 1. For example, surface roughness can be used as an index of surface smoothness. Usually, the contact portion (pre-treated portion 5) has a larger surface roughness value than the periphery.
[0047] Regarding b), the relationship between the amount of wetting agent in the contact part with the anode unit on the surface of the concrete structure and the surrounding area can be examined by comparing the electrical resistance values of both parts. Specifically, the electrical resistance value is measured for each of the contact part (pretreated part 5) and the surrounding area of the contact part on the surface of the concrete structure 1 by a method conforming to JSCE-G581-2018 (Draft method for testing the electrical resistivity of concrete by the four-electrode method). If the electrical resistance value of the pretreated part 5 is smaller than that of the surrounding area, it can be estimated that the pretreated part 5 contains a larger amount of wetting agent than that of the surrounding area. In measuring such electrical resistance value, the "peripheral area of the pretreated part 5" to be compared with the pretreated part 5 is an area within 200 mm outward from the contour of the pretreated part 5. In addition, the "electrical resistance value of the surrounding area of the pretreated part 5" is the minimum electrical resistance value measured at any three points in the surrounding area. That is, when the electrical resistance value of the pre-treated area 5 is smaller than the minimum value of the electrical resistance values at any three points in its surrounding area, it can be estimated that the pre-treated area 5 contains a greater amount of wetting agent than the surrounding area. EXAMPLES
[0048] [Investigation of the relationship between the impregnation depth of surface impregnating material and electrical resistance value] The relationship between the impregnation depth of the surface impregnation material and the electrical resistance was investigated for concrete structures to which the cathodic protection method of the present invention can be applied, i.e., "concrete structures having a concrete body in which steel materials are embedded and a water-repellent, breathable layer provided on the surface of the concrete body, the water-repellent, breathable layer containing a silane-based or silane-siloxane-based surface impregnation material" (hereinafter also referred to as "water-repellent treated concrete structures"). Specifically, a silane-siloxane-based surface impregnation material was applied to the surface of the mortar test specimen, and the electrical resistance value was measured at each depth from the applied surface to examine the conditions under which cathodic protection would be applicable. As shown in Figure 4, the mortar test specimen was a rectangular column with a length of 160 mm in the longitudinal direction L, a length of 40 mm in the width direction W, and a length of 40 mm in the height direction H. It was manufactured using ordinary Portland cement as the cement, with a water-cement ratio (W / C) of 50% and a sand-cement ratio (S / C) of 3.0. The mortar test specimen without the surface impregnation material was designated "Sample A" (blank). In addition, a silane-siloxane-based surface impregnation material was applied to one surface of the mortar test specimen at a wet weight of 0.2 kg / m per application. 2 The specimen was designated as "Sample B." In addition, a surface impregnating material of alkylalkoxysilane (silane type) was applied to one surface of the mortar specimen in an amount of 0.3 L / m2 (wet weight) per application. 2 The specimen that was applied twice under the condition of 0.1 mm to 0.5 mm was designated as "Sample C". Samples B and C are concrete structures that have been treated for water repellency. The number of samples was three for each of the three types of samples A to C (total number of samples was nine). As shown in FIG. 4, each of samples A to C was divided into three in the longitudinal direction L to obtain three divided bodies S1 to S3. Two divided bodies S1 and S2 (length in the longitudinal direction L: 30 mm) located at both ends of the longitudinal direction L were used as samples for measuring impregnation depth, and the remaining divided body S2 (length in the longitudinal direction L: 100 mm) was used as a sample for measuring electrical resistance. In FIG. 4, the surface designated by the reference symbol 40 is the starting surface for measuring electrical resistance, and in samples B and C, it is also the applied surface of the surface impregnation material.
[0049] The impregnation depth of the surface impregnating material was measured for each of the samples A to C for measuring the impregnation depth by a method conforming to JSCE-K571-2013 (test method for surface impregnation material). Specifically, the impregnation depth measuring sample was split at the center in the longitudinal direction L and immersed in tap water for 1 minute, and then the sample was visually observed, and the part that had not changed color compared to before immersion was regarded as the impregnated part of the surface impregnating material, and the thickness of the impregnated part (length in the height direction H starting from the measurement start surface 40) was measured with a vernier caliper. The impregnated part corresponds to a water-repellent breathable layer, and the thickness of the impregnated part can be regarded as the thickness of the water-repellent breathable layer. The measurement results were as follows. Sample A: The impregnated portion could not be confirmed (the thickness of the impregnated portion was zero). Sample B: The thickness of the impregnated portion was 1.77 to 3.70 mm (average value 2.71 mm). · Sample C: The thickness of the impregnated portion was 4.33 to 7.30 mm (average value 5.45 mm).
[0050] For each of the samples A to C, the electrical resistance measurement samples were measured at the measurement start surface 40 and at a position spaced a predetermined distance from the measurement start surface 40 in the height direction H by a method conforming to JSCE-G581-2018 (Concrete Electrical Resistivity Test Method by Four-Electrode Method (Draft)). Specifically, for each sample, first, the electrical resistance of the measurement start surface 40 was measured, and then the entire measurement start surface 40 was ground with a disk sander or abrasive paper, and then the electrical resistance of the sample surface after grinding was measured, and then the entire sample surface was ground in the same manner. Thereafter, the measurement of the electrical resistance and the grinding of the sample surface were repeated, and the electrical resistance of the sample was measured at a position spaced a predetermined distance from the measurement start surface 40 (sample surface before grinding) in the height direction H. The distance in the height direction H between the measurement start surface 40 and the position where the electrical resistance value is measured, i.e., the depth from the sample surface before searching to the measurement position (hereinafter also referred to as the "grinding depth"), was determined by measuring the thickness (total length in the height direction H) of any nine points on each ground sample with a vernier caliper and subtracting the average value of the thicknesses of the nine points from the thickness (total length in the height direction H) of the sample before grinding.
[0051] FIG. 5 shows a graph showing the relationship between the grinding depth and the electrical resistance value in sample A. FIG. 6 shows a graph showing the same relationship for sample B, and FIG. 7 shows a graph showing the same relationship for sample C. A1, A2, and A3 in FIG. 5 show three samples of sample A, and these three samples A1, A2, and A3 are all under the same conditions. B1, B2, and B3 in FIG. 6 show three samples of sample B, and these three samples B1, B2, and B3 are all under the same conditions. C1, C2, and C3 in FIG. 7 show three samples of sample C, and these three samples C1, C2, and C3 are all under the same conditions. As shown in Figure 5, the electrical resistance value of sample A (concrete structure without water-repellent treatment), which was not coated with a surface impregnation material, was relatively high at 60 to 5,000 kΩ·cm when the grinding depth was 0.10 mm or less, and was an almost constant value of around 40 kΩ·cm when the grinding depth was 0.11 mm or more. As shown in Fig. 6, the electrical resistance value of sample B was a maximum of 13,000 kΩ·cm on the sample surface before grinding (the surface coated with the surface impregnating material), but it decreased as the grinding depth increased, and showed an almost constant value of around 40 kΩ·cm when the grinding depth was 1.0 mm or more. As shown in Figure 7, the electrical resistance value of sample C was 130 to 1700 kΩ·cm on the sample surface before grinding (the surface coated with the surface impregnating material), exceeded 180 kΩ·cm when the grinding depth was within a range of about 0.9 mm, was about 100 kΩ·cm when the grinding depth was 1.0 mm, and gradually decreased after the grinding depth exceeded 1.0 mm, finally showing an almost constant value of around 40 kΩ·cm. As mentioned above, the thickness of the impregnated portion of the surface impregnation material (thickness of the water-repellent, breathable layer) was 2.71 mm on average for sample B and 5.45 mm on average for sample C, whereas the electrical resistance value of both samples B and C at a position approximately 1.0 mm away in the height direction H from the sample surface before grinding (the surface where the surface impregnation material was applied), i.e., in the area where the surface impregnation material had impregnated and a water-repellent, breathable layer had been formed, was approximately the same as the minimum electrical resistance value of 40 kΩ·cm of sample A, which had not been coated with a surface impregnation material. From the above results, it can be seen that when the cathodic protection method of the present invention is applied to a water-repellent treated concrete structure having an existing water-repellent and air-permeable layer on its surface, if the surface layer including the water-repellent and air-permeable layer is removed from the concrete structure in the pretreatment process, the amount of surface layer to be removed is sufficient, regardless of the thickness of the water-repellent and air-permeable layer, with a maximum thickness of 1.0 mm.
[0052] [Examples 1 to 3] The water-repellent treated concrete structure was subjected to the above-mentioned pretreatment step and anode installation step in that order to obtain an electrochemically protected structure for the concrete structure. Specifically, first, a concrete specimen was produced as the base for the water-repellent treated concrete structure. Referring to Fig. 4, the concrete specimen had a rectangular column shape with a length in the longitudinal direction L of 220 mm, a length in the width direction W of 100 mm, and a length in the height direction H of 100 mm, and had a polished round steel bar (steel material) with a diameter of 19 mm extending in the longitudinal direction L through the center of both the width direction W and the height direction H. The concrete specimen used ordinary Portland cement as the cement, had a water-cement ratio (W / C) of 55%, and a chloride ion concentration of 6 kg / m 3 The concrete specimens were subjected to wet curing for 270 days, and then dried in a thermo-hygrostat at an atmospheric temperature of 23°C and a humidity of 50% for 9 days. After that, a silane-siloxane-based surface impregnation material was applied to one side of the concrete specimens at a wet weight of 0.2 kg / m per application. 2 The coating was applied once under the above conditions and then dried for 7 days to form a water-repellent, breathable layer, thereby obtaining a water-repellent treated concrete structure. Next, sandblasting was used as a grinding means to blast the entire surface of the water-repellent and air-permeable layer of the water-repellent treated concrete structure, and a predetermined amount of the surface layer including the water-repellent and air-permeable layer was removed (pretreatment step (surface layer removal step)). The timing and degree of the blasting (amount of surface layer removed) were appropriately changed depending on the embodiment. This will be described later. In Example 3, after the blasting process, a pretreatment liquid was applied to the blasted portion (the portion of the concrete structure from which the surface layer had been removed) (pretreatment step (pretreatment liquid application step)). The pretreatment liquid contained magnesium chloride as an electrolyte, a wetting agent (a silicone surfactant, "Polyflow KL-100" manufactured by Kyoeisha Chemical Co., Ltd.), and water. Magnesium chloride was applied at a rate of 10 g / m to the portion to which the pretreatment liquid was applied. 2 , 0.5g / m of wetting agent 2 The composition and amount of the pretreatment liquid applied were adjusted so that the pretreatment liquid could be applied. Next, an anode unit including an anode material was directly installed on the blasted portion of the water-repellent treated concrete structure, and the anode material and the polished round steel (steel material) were connected with a conductor via a fixed resistor of 10 Ω (anode installation process).
[0053] The anode unit has a structure basically similar to that of the anode unit 6 shown in Fig. 1(c), and includes an anode material, a backfill, and a container for containing and protecting them. The main components of the anode unit are as follows: Anode material: Zinc alloy anode material ("ZINAP" manufactured by Nakabohtec Co., Ltd.), length in the longitudinal direction L: 220 mm, length in the width direction W: 55 mm, length in the height direction H: 21 mm. Backfill: A water-retentive body in which a cellulose fiber assembly is impregnated with 36 ml of saturated magnesium chloride aqueous solution, with a length in the longitudinal direction L of 220 mm, a length in the width direction W of 55 mm, and a length in the height direction H of 21 mm. The cellulose fiber assembly is made of a pulp nonwoven fabric ("Hato Sheet XCA" manufactured by Oji Kinocloth Co., Ltd., with a basis weight of 1800 g / m 2 ) is used. -Container: A trough-shaped container made of fiberglass reinforced plastic (FRP), with a length in the longitudinal direction L of 220 mm, a length in the width direction W of 100 mm (container section 60 mm, flange section 40 mm), and a length in the height direction H of 21 mm.
[0054] <Measurement test of anticorrosion current> In the cathodic protection structures of Examples 1 to 3, the anticorrosive current between the anode material and the steel material was measured periodically, and the measured value was used to calculate the current per unit area of the concrete structure (1 m 2 The current density per unit area was calculated. The results are shown in Figure 8. In Figure 8, "No. 1" indicates Example 1, "No. 2" indicates Example 2, and "No. 3" indicates Example 3. "Suspension period" in Figure 8 refers to the period when the passage of electricity through the cathodic protection structure was stopped. In Example 1, the surface layer removal step (the blasting process) was not carried out from the start of measurement until the 26th day, but was carried out on the 27th day, and 0.82 mm of the surface layer including the water-repellent and breathable layer was removed. That is, in Example 1, the amount of the surface layer removed was zero during the period from the start of measurement until the 26th day (before the suspension period), and during the period from the start of measurement until the 27th day (after the suspension period), 0.82 mm of the surface layer had been removed from the beginning. In each of Examples 2 and 3, a surface layer removing step (blasting) was carried out before starting the measurement of the current density, and the surface layer including the water-repellent and breathable layer was removed by 0.05 mm in thickness. That is, each of Examples 2 and 3 was subjected to the measurement test of the anticorrosive current in a state in which 0.05 mm of the surface layer was removed from the beginning, and this state was maintained during the measurement period. Table 1 below shows the conditions of Examples 1 to 3 in the measurement test.
[0055] [Table 1]
[0056] As shown in FIG. 8, in Example 1, the current density was low before the shutdown period when the surface layer was not removed, but after the shutdown period when the surface layer was removed, a high current density was shown, and the anticorrosion current required to obtain a sufficient anticorrosion effect was flowing. Furthermore, when comparing Example 1 and Example 2 after the shutdown period, Example 1, in which a larger amount of the surface layer was removed, showed a higher current density, indicating that there is a positive correlation between the amount of the surface layer removed and the current density (electrical protection effect). Furthermore, when comparing Example 2 and Example 3, Example 3, in which the pretreatment liquid application step was carried out, showed a higher current density, which indicates that the pretreatment liquid application step is effective in improving the current density (electrical protection effect). [Explanation of symbols]
[0057] 1. Concrete Structures 2 Steel material 3. Concrete body 4. Water-repellent and breathable layer 5 Pre-treated area (anode unit installation space) 6 Anode Unit 61 Anode material 63 Backfill 64 Containment Unit 10,10A Electrical corrosion protection structure
Claims
1. A method for cathodic protection of a concrete structure, comprising: a concrete body having a steel material embedded therein; and a water-repellent, breathable layer provided on the surface of the concrete body, the water-repellent, breathable layer including a silane-based or silane-siloxane-based surface impregnation material, a pretreatment step of removing a surface layer including the water-repellent and air-permeable layer from the concrete structure, or applying a pretreatment liquid including an electrolyte and a wetting agent that modifies the surface wettability of the water-repellent and air-permeable layer to the surface of the concrete structure; an anode installation step of directly installing an anode unit including an anode material on the portion of the concrete structure that has been subjected to the pretreatment step, and electrically connecting the anode material and the steel material; A method for electrochemical protection of a concrete structure, in which the water-repellent, breathable layer is not formed in an area of the concrete structure that overlaps in plan view with the anode unit installed in the anode installation step.
2. 2. The method for cathodic protection of a concrete structure according to claim 1, wherein the portion of the concrete structure that has been subjected to the pretreatment step has an electrical resistance value of 1 to 100 kΩ·cm.
3. 3. The method for cathodic protection of a concrete structure according to claim 1, wherein when the surface layer is removed from the concrete structure in the pretreatment step, the amount of the surface layer removed is 1.0 mm or more in thickness.
4. When the pretreatment liquid is applied to the surface of the concrete structure in the pretreatment step, the electrolyte is applied to the portion to which the pretreatment liquid is applied at a rate of 5 g / m 2 The above wetting agent is 0.02 g / m 2 The method for electrical corrosion protection of a concrete structure according to claim 1 or 2, wherein the above is provided.
5. 3. The cathodic protection method for a concrete structure according to claim 1, wherein in the pretreatment step, the surface layer is removed from the concrete structure, and then the pretreatment liquid is applied to the portion from which the surface layer has been removed.
6. When the surface layer is removed from the concrete structure in the pretreatment step, the amount of the surface layer removed is 0.05 mm or more in thickness, The electrolyte is applied to the portion from which the surface layer has been removed at a rate of 5 to 30 g / m. 2 , the wetting agent is 0.02 to 2.0 g / m 2 The method for electrical protection of a concrete structure according to claim 5, further comprising the step of:
7. A cathodic protection structure for a concrete structure manufactured by the cathodic protection method according to claim 1 or 2, An electrical corrosion protection structure for a concrete structure, wherein the contact portion between the anode unit and the surface of the concrete structure is ground off, or the contact portion has a higher content of the wetting agent than the surrounding area of the contact portion on the surface.
Citation Information
Patent Citations
Electrolytic protection method
JP2011236485A
Electric anticorrosion method for reinforced concrete structure
JP2012144771A